Methods of testing materials at the contact dynamic loading - Хімко, А.М.; Бородій, В.М.; Якобчук, О.Є. (Proceedings of National Aviation University (archive), 2008)
A technique of test of materials and coatings at a contact dynamic loading is shown. Depending on the conditions of loading there are dynamic loading with slipping and dynamic loading with the reversed-cyclic sliding. The comparative tests of plasma and electrospark covering are conducted. It is certain that the most wear-resistant coating is plasma coating of molybdenum.